Challenges of managing food allergy in the developing world() - Hossny, Elham (World Allergy Organ J, 2019)
Food allergy (FA) is currently a significant health care problem in the developing world. Widely varying study populations and methodologies, the use of surrogate markers such as self report or hospitalization rates due to anaphylaxis rather than objective methods, limits robust estimation of FA prevalence in low income settings. Also, allergy is under-recognized as a clinical specialty in the developing world which compromises the chance for accurate diagnosis. In this review, most published data on food allergens from developing or low income countries are displayed. The diagnostic challenges and limitations of treatment options are discussed. It seems that FA is an under-appreciated health care issue in the developing world, and accurate determination of its burden in low-income settings represents an important unmet need. Multicenter surveillance studies, using standardized methodologies, are, therefore, needed to reveal the true extent of the problem and provide epidemiological clues for prevention. Preventive strategies should be tailored to fit local circumstances in different geographic regions. In addition, studying the gene environment interactions and impact of early life microbiota on the expression of FA in developing communities would be worthwhile. Efforts and resources should be directed toward public health education and training of health care providers dealing with food allergic patients.